Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1300/j091v23n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sustainable Forestry Initiative on the Quality, Abundance, and Configuration of Wildlife Habitats

Abstract: ABSTRACT. We analyzed the effects of landscape measures within thefox squirrel (Sciurus niger) and gray squirrel (Sciurus carolinensis).Habitat suitability of the landscape in general increased with the implementation of SFI measures and habitat conditions were more diverse and even. Fragmentation and establishment of narrow and elongated habitat areas in a network configuration were the main consequences of the implementation of SFI measures in terms of habitat spatial structure. These changes were usually no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…For each scenario, five replicate runs were conducted using independently generated random number seeds. Partial studies on the effects of SFI on the landscape processes in intensively managed forested landscapes in East Texas are available in Azevedo et al (2005a), Azevedo et al (2005b), and Azevedo et al (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each scenario, five replicate runs were conducted using independently generated random number seeds. Partial studies on the effects of SFI on the landscape processes in intensively managed forested landscapes in East Texas are available in Azevedo et al (2005a), Azevedo et al (2005b), and Azevedo et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…The habitats were modeled with HSI models using data provided by the growth and yield models and in few cases from assumptions based upon published data. Application of the HSI models is described in detail in Azevedo et al (2006). At the landscape level, HSI was calculated from the GIS coverages resulting from the landscape simulations.…”
Section: Wildlife Habitatsmentioning
confidence: 99%
“…However, direct comparisons are lacking for southern pine forest landscapes, and much of our supposition that riparian areas increase species richness and diversity is inferred from our knowledge of individual species biology. For example, Azevedo et al (2006) modeled SFI practices in an East Texas watershed and reported that implementation of SMZs was particularly beneficial in improving habitat suitability for an array of indicator wildlife species. Recommendations for SMZ widths to protect water quality may not be appropriate for meeting some objectives for wildlife communities.…”
Section: Wildlife Relationships With Smzsmentioning
confidence: 99%